Nitric Oxide Has a Concentration-Dependent Effect on the Cell Cycle Acting via EIN2 in Arabidopsis thaliana Cultured Cells - Novikova, Galina V.; Mur, Luis A. J.; Nosov, Alexander V.; Fomenkov, Artem A.; Mironov, Kirill S.; Mamaeva, Anna S.; Shilov, Evgeny S.; Rakitin, Victor Y.; Hall, Michael A. (Frontiers in Physiology, 2017)
Ethylene is known to influence the cell cycle (CC) via poorly characterized roles whilst nitric oxide (NO) has well-established roles in the animal CC but analogous role(s) have not been reported for plants. As NO and ethylene signaling events often interact we examined their role in CC in cultured cells derived from Arabidopsis thaliana wild-type (Col-0) plants and from ethylene-insensitive mutant ein2-1 plants. Both NO and ethylene were produced mainly during the first 5 days of the sub-cultivation period corresponding to the period of active cell division. However, in ein2-1 cells, ethylene generation was significantly reduced while NO levels were increased. With application of a range of concentrations of the NO donor, sodium nitroprusside (SNP) (between 20 and 500 μM) ethylene production was significantly diminished in Col-0 but unchanged in ein2-1 cells. Flow cytometry assays showed that in Col-0 cells treatments with 5 and 10 μM SNP concentrations led to an increase in S-phase cell number indicating the stimulation of G1/S transition. However, at ≥20 μM SNP CC progression was restrained at G1/S transition. In the mutant ein2-1 strain, the index of S-phase cells was not altered at 5–10 μM SNP but decreased dramatically at higher SNP concentrations. Concomitantly, 5 μM SNP induced transcription of genes encoding CDKA;1 and CYCD3;1 in Col-0 cells whereas transcription of CDKs and CYCs were not significantly altered in ein2-1 cells at any SNP concentrations examined. Hence, it is appears that EIN2 is required for full responses at each SNP concentration. In ein2-1 cells, greater amounts of NO, reactive oxygen species, and the tyrosine-nitrating peroxynitrite radical were detected, possibly indicating NO-dependent post-translational protein modifications which could stop CC. Thus, we suggest that in Arabidopsis cultured cells NO affects CC progression as a concentration-dependent modulator with a dependency on EIN2 for both ethylene production and a NO/ethylene regulatory function.